Designing Equitable Worlds: Six Orientations to Evoke the Future. - Carey, Hillary (Design Issues)
This article proposes that designers can enhance and extend the efforts for social change by transforming concepts of equity and justice into material, informative, and interactive experiences. The framework introduced here outlines six orientations for evoking future outcomes in the present moment. These orientations stem from a synthesis of techniques from disciplines with varying perspectives on world-building (rhetoric, theology, political science, and art). It identifies multiple ways to evoke the future in the present. Shared and iterated through a series of workshops in racial justice contexts, the framework offers a structure for advocates to recognize how they are already building better worlds and how they can translate future visions into near-term communication pieces that engage people in their mission.